Fourier-transform infrared spectroscopy/attenuated total reflectance analysis for the degree of conversion and shear bond strength of Transbond XT adhesive system - Masood TM; Abbassy MA; Bakry AS; Matar NY; Hassan AH (Dove Medical Press, 2018)
Taha Mohammed Masood,1,2 Mona Aly Abbassy,3,4 Ahmed Samir Bakry,5,6 Naof Yessen Matar,3 Ali Habib Hassan3 1Dental and Maxillofacial Department, Saudi German Hospital, Jeddah, Saudi Arabia; 2Orthodontics Department, Faculty of Dentistry, Batterjee Medical College, Jeddah, Saudi Arabia; 3Department of Orthodontics, Faculty of Dentistry, King Abdulaziz University, Jeddah, Saudi Arabia; 4Orthodontics Department, Faculty of Dentistry, Alexandria University, Alexandria, Egypt; 5Operative and Esthetic Dentistry Department, Faculty of Dentistry, King Abdulaziz University, Jeddah, Saudia Arabia; 6Conservative Dentistry Department, Faculty of Dentistry, Alexandria University, Alexandria, Egypt Objective: The objectives of this study were to evaluate the degree of conversion (DC) for Transbond XT curing light of intensity 1,600 mW/cm2 by using variable curing durations and to determine the effect of the tested curing durations adopted in the current experiment on shear bond strength of Transbond XT resin cement. Materials and methods: A total of 85 orthodontic ceramic brackets (Victory series; 3M Unitek) were utilized in the current experiment. The bonding system used in the current study was Transbond XT Primer followed by Transbond PLUS Color Change Adhesive (3M Unitek) that cured for 3, 6, and 9 seconds. The method was done by polymerization of the adhesive under a ceramic bracket for 40 ceramic brackets. The other 45 brackets were divided into three groups (n=15) according to the curing time duration (3, 6, and 9 seconds). The bonded specimens in each group were debonded using a shear load applied at the bracket bases by the blades of an Instron universal testing machine (ElectroPlus E1000; Instron) and directed in an occlusogingival direction with a crosshead speed of 0.5 mm/min utilizing 50 kg load cell. Results: One-way ANOVA revealed that 6 and 9 seconds curing by the Ortholux light cure scored significantly higher values when compared to the 3 seconds curing. Conclusion: Curing the Transbond XT for 6 and 9 seconds recorded a significant improvement of bond strength and DC. Keywords: orthodontics, FTIR/ATR, degree of conversion, bond strength